Biosynthesis of a biopolymer poly(3-hydroxybutyrate) from a mixture of palm oil and 2-butanol as carbon sources - Djamaan, Akmal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Polyhydroxybutyrate [P(3HB)] are synthesized as carbon and energy reserve materials by many types of microorganisms under certain environmental condition. These biosynthetic polyesters have much received attention as they can be considered to be a source for developing novel biodegradable plastic materials for pharmaceutical, medical and biodegradable packages industries. In this case, Erwiniasp. USMI-20, a locally soil isolated microorganism has been found to accumulate P(3HB) in its cells during growth on mineral-media with a mixture of palm oil and 2-butanol as carbon source. Fermentation process was conducted through a feedbatch cultivation under aerobic condition at pH 7.0, incubation temperature 30 oC, and agitation rate of 200 rpm for 48 hours. The characterization of the polymer production was based on cell growth (biomass) and polymer content detected by a gas chromatography methode. Result showed that from a mixture of palm oil:2-butanol (4.62g/L+0.89g/L) produced P(3HB) of 50.86 %w/w with biomass of 5.82g/L; a mixture of palm oil:2-butanol (4.62g/L+1.65g/L) produced P(3HB) of 57,77% w/w with biomas of 6.01g/L, a mixture of palm oil:2-butanol (4.62g/L+2.48g/L) produced P(3HB) of 55.85%w/w with biomass of 6.57g/L, a mixture of palm oil:2-butanol (4.62g/L+3.29 g/L) produced P(3HB) of 56.37% w/w with biomass of 6.67g/L and a mixture of palm oil:2-butanol (4.62g/L+4.12g/L) produced P(3HB) of 47.70% w/w with biomass of 6.33g/LKey words:biopolymer, poly(3-hydroxybutyrate), palm oil, and n-butanol.